Living in the COVID-19 Pandemic Podcast - Abrantes, Maria Luiza Sansão (Universidade Estadual Paulista (Unesp), 2020)
In this episode of the Foreign Language Learner Podcast, a student in the second year of Translation Studies at Unesp - São José do Rio Preto talks about living in the Covid19 pandemic.
Nível de proficiência de produção oral autoavaliado pelo aluno: C1
Keywords: COVID19 Pandemic; English language Pronunciation by foreigners; COVID-19; Pandemias; Língua inglesa Pronúncia estrangeira